Conceptual and Preliminary Design Innovation of a Multipurpose Palm Fruit Vessel for Inland Plantation Waterways in Muara Kaman - Suardi Suardi; Jamal Jamal; Arwis Irmandana; Alamsyah Alamsyah; Wira Setiawan; Chris Jeremy Verian Sitorus; Jusma Wahidah; Cindy Lionita Agusty; Faisal Mahmuddin (Indonesian Journal of Maritime Technology, 2026)
Oil palm fruit production in East Kalimantan continues to increase in line with high market demand. This situation demands efficient transportation facilities to transport the harvest from plantation areas. Furthermore, annual forest fires, particularly in peatland areas, are often difficult to manage due to limited land access. Based on these two challenges, this study proposes the design of a multipurpose vessel capable of both transporting oil palm fruit and supporting firefighting. The vessel is designed with main dimensions of L = 20 m, B = 4.9 m, H = 2 m, T = 1.5 m, and an operating speed of 8 knots. The cargo hold has a carrying capacity of 67.3 tons with a single trip distance of 12.3 km. The main innovation developed is a conveyor belt with hydraulic arms to increase the efficiency of the oil palm fruit loading and unloading process in the plantation area. Furthermore, the vessel is equipped with an external firefighting system with a capacity of 90 m³/hour with a horizontal spray range of 30 meters and a vertical height of 20 meters. The fire monitor operates using 7 kW of power to generate sufficient pressure to extinguish fires in areas difficult to reach from the riverbank. This multipurpose vessel is designed to provide an integrated solution for the oil palm plantation logistics chain while improving the response to forest fires in the Muara Kaman District.